2017
DOI: 10.1158/0008-5472.can-16-1004
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A and NF-κB Survival Pathway Drive Chemoresistance in Acute Myeloid Leukemia via the TRAF-Interacting Protein TIFA

Abstract: Aurora A-dependent NF-kB signaling portends poor prognosis in acute myeloid leukemia (AML) and other cancers, but the functional basis underlying this association is unclear. Here, we report that Aurora A is essential for Thr9 phosphorylation of the TRAF-interacting protein TIFA, triggering activation of the NF-kB survival pathway in AML. TIFA protein was overexpressed concurrently with Aurora A and NF-kB signaling factors in patients with de novo AML relative to healthy individuals and also correlated with po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 53 publications
1
49
0
Order By: Relevance
“…In line with this concept, the role of NF-κB and its downstream molecules in the modulation of lung cancer cell cycle and survival was explored in this study. In agreement with previous reports [15,27], we established that the silencing of TIFA promoted apoptosis and inhibited the cell migration of the lung cancer cell lines. Moreover, it attenuated the phosphorylation of IKK, IκB, and p65, and decreased the levels of Bcl-2, cyclin D1, and CDK4, but increased those of p21, p53, and cleaved caspase-3.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 93%
See 1 more Smart Citation
“…In line with this concept, the role of NF-κB and its downstream molecules in the modulation of lung cancer cell cycle and survival was explored in this study. In agreement with previous reports [15,27], we established that the silencing of TIFA promoted apoptosis and inhibited the cell migration of the lung cancer cell lines. Moreover, it attenuated the phosphorylation of IKK, IκB, and p65, and decreased the levels of Bcl-2, cyclin D1, and CDK4, but increased those of p21, p53, and cleaved caspase-3.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 93%
“…Cellular Physiology and Biochemistry reported that TIFA was expressed in acute myeloid leukemia (AML), and suppression of TIFA in AML cell lines by siRNA successfully decreased the leukemic cell growth and chemotherapy resistance [15]. By contrast, Shen et al reported that the expression of TIFA in hepatocellular carcinoma (HCC) cells was lower than that in normal liver control cells; furthermore, the reconstitution of TIFA expression promoted the apoptosis of the HCC cells [14].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Because unresolved innate immunity in the endothelium plays a pathophysiological role in vascular impairments, targeting TIFA may provide a new therapeutic strategy for vascular diseases. In light of this, Aurora A kinase has recently been shown to phosphorylate Thr9 of TIFA as well, and targeting TIFA can enhance therapeutic efficacies in the treatment of acute myeloid leukemia (44).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that AURKB overexpression can lead to multinuclear cells and polyploidy [47] and is highly correlated with genomic instability and poor prognosis in neuroblastoma [48]. Other studies have shown that AURKA can promote the expression of anti-apoptotic proteins in tumor cells, and this gene can be used as a biomarker and target for a variety of tumor treatments [4951].…”
Section: Disscusionmentioning
confidence: 99%